Multiharmonic small-signal modeling of low-power PWM DC-DC converters - Wang, Ya (2017)
Small-signal models of pulse-width modulation (PWM) converters are widely used for analyzing stability and play an important role in converter design and control. However, existing small-signal models either are based on averaged DC behaviors, and hence are unable to capture frequency responses that are faster than the switching frequency, or greatly approximate these high-frequency responses. We address the severe limitations of the existing models by proposing a multiharmonic model that provides a complete small-signal characterization of both DC averages and high-order harmonic responses. The proposed model captures important high-frequency overshoots and undershoots of the converter response, which are otherwise unaccounted for by the existing techniques. In two converter examples, the proposed model corrects the misleading results of the existing models by providing truthful characterization of the overall converter AC response and offers important guidance for converter design and closed-loop control.